Supported self-care for children and adolescents with chronic disease and their families - Leiliane Teixeira Bento Fernandes; Vanessa Medeiros da Nóbrega; Maria Elizabete de Amorim Silva; Amanda Narciso Machado; Neusa Collet
ABSTRACT Objective: analyze the scientific production between 2006 and 2015 on strategies for supported self-care by children and adolescents with chronic disease and their families. Method: integrative review of the literature conducted July and August 2016 in the databases: BDENF, LILACS, IBECS, ADOLEC, MEDLINE/PubMed and SCIELO. The 27 selected studies were analyzed and categorized into the five pillars of supported self-care: evaluation, counseling, agreement, care and accompaniment. Results: only two studies covered all five pillars, evaluation was considered most, but accompaniment was essential for adherence to the therapeutics of the goal plan. There was a prevalence of actions to evaluate the emotional state of the child/adolescent/family and technological interventions to empower the individual in self-care. Final considerations: these actions are concentrated in countries with health systems directed to the health needs of people with chronic disease. In Brazil, this is still incipient, since the actions are focused on exacerbation.